Pragmatic Production of Third Language Learners of English: A Focus on Request Acts Modifiers - Jorda, Maria Pilar Safont (International journal of multilingualism, 2005)
The present study examines pragmatic production of monolingual (L1 Castilian) and bilingual (L1 Catalan, L2 Castilian) learners of English in a foreign language learning context, that of the Valencian Community in Spain. We particularly focused on proficiency-level effects and on the role of the task type in the use of request acts peripheral modification devices. We ascertained participants' degree of bilingual competence by means of a bilingualism test, which was designed on the basis of previous research (Li Wei, 2000). Additionally, a level placement test was distributed to our participants, and their performance was assessed on the basis of the ACTFL proficiency guidelines. Data for our analysis were collected by means of an open discourse completion test and a role-play task. Results from our analysis point to differences between bilinguals' and monolinguals' use of peripheral modification devices. More specifically our study shows that (1) L3 learners of English employed request modifiers more frequently and appropriately than L2 English learners, (2) intermediate learners performed better than beginner learners both in the oral and written task, and (3) the written task allowed for a wider use of peripheral modification devices although results also show that internal modification devices were highly employed in the oral task. Findings from our study seem to call for further research on the pragmatic competence of third language learners of English thereby considering other speech acts or pragmatic aspects and also by analysing subjects from different linguistic backgrounds.